Study of a Process for the Extraction of a Betacyanin-Based Nature Colouring from Viet Nam Red Dragon - Luu, Thi Lan Anh; Nguyen, Ngoc Trung; Nguyen, Thi Tuyet Mai; Vo, Thach Son (Old Journal, 2019)
Dragon fruit has gradually become one of the most popular fruits of the Vietnamese. Dragon fruit is not only a nutritiou fruit, it is also a source of betacyanin pigments used in foods, pharmaceuticals and Dye-sensitized solar cell (DSSC). In this study, batacyanin was extracted from the pulp of the red dragon fruit with the aid of ultrasound. Extraction results were analyzed using UV-Vis absorption spectrometry method. Results showed that the optimal technical conditions for for the extraction are: solvent is, a mixture of distilled water and absolute alcohol with ratio H₂O: C₂H₅OH = 1: 1; temperature T = 40℃; sample mass m = 12.5 g; extracting time t = 40 mins. Concentration of betacyanin was about 334 mg/l.